Perceptions of Controlling Teaching Behaviors and the Effects on the Motivation and Behavior of High School Physical Education Students - Moreno-Murcia, Juan Antonio; Huéscar Hernández, Elisa; Ruiz, Lorena (International journal of environmental research and public health, 2018)
The purpose of this study was to examine the effects of controlling teacher behavior on high school physical education students’ global intrinsic motivation, perceptions of the importance of the subject matter, intentions to be physically active, level of physical activity, and life satisfaction. The sample in this study was comprised of 416 Spanish high school students. Support for the study’s expectations was provided through structural regression analysis. The analysis revealed that a controlling teaching style was negatively associated with the global intrinsic motivation of the students. In turn, global intrinsic motivation predicted the perceived importance of the subject matter, which explained physical activity intentions. Physical activity intentions were positively associated with level of physical activity, which, in turn, explained life satisfaction. The knowledge obtained in this study can be of benefit to teachers and can be beneficial to the design of more adaptive learning environments for students.